2013
DOI: 10.1016/j.breast.2013.07.042
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated partial breast irradiation using 3D conformal radiotherapy: Toxicity and cosmetic outcome

Abstract: APBI using 3D-CRT is technically feasible with very low acute and late toxicity. Long-term results are needed to assess its efficacy in reducing the incidence of breast relapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
3
0
1
Order By: Relevance
“…Prior trials of external beam APBI assessing cosmetic subdomains have used varying scales and evaluated different subdomains, making comparisons across studies difficult. These included the use of RTOG, 19,39 CTCAE, 14,22,[40][41][42][43] and European Organization for Research and Treatment of Cancer 44 scales, as well as the use of a Multi-Skin-Center MC-750-B2 probe to objectively assess fibrosis in 1 study. 18 In a phase 2 trial of 158 patients at the University of Kentucky assessing once weekly 30 Gy/5 fractions (later amended to 28.5Gy/5 fractions) WBI, a similar 9 parameter Breast Cancer Treatment Outcome Scale subdomain scale was used, and they reported volume loss (28%), retraction (18%), and scarring (18%) as being the subdomains most frequently affecting cosmesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior trials of external beam APBI assessing cosmetic subdomains have used varying scales and evaluated different subdomains, making comparisons across studies difficult. These included the use of RTOG, 19,39 CTCAE, 14,22,[40][41][42][43] and European Organization for Research and Treatment of Cancer 44 scales, as well as the use of a Multi-Skin-Center MC-750-B2 probe to objectively assess fibrosis in 1 study. 18 In a phase 2 trial of 158 patients at the University of Kentucky assessing once weekly 30 Gy/5 fractions (later amended to 28.5Gy/5 fractions) WBI, a similar 9 parameter Breast Cancer Treatment Outcome Scale subdomain scale was used, and they reported volume loss (28%), retraction (18%), and scarring (18%) as being the subdomains most frequently affecting cosmesis.…”
Section: Discussionmentioning
confidence: 99%
“…Other trials of external beam APBI have similarly reported low rates of CTCAE grade 1þ hyperpigmentation (3%-18%). 40,41,43,44 Although 9 distinct cosmetic subdomains were assessed in this trial, some subdomain scores may not be reliable via digital photography alone without physical examination correlation. When evaluating the Fleiss k scores at all time points, all subdomains reached significance except for telangiectasia.…”
Section: Discussionmentioning
confidence: 99%
“…APBI with 3D-CRT is noninvasive and linear accelerator based, delivered with modern techniques, and may be less costly. Different studies have reported outcomes with APBI, [7][8][9][10][11][12][13] and few have reported unfavorable outcomes for cosmesis. [16][17][18][19] This study was designed to compare APBI with WBI after BCS in women with breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Entre as técnicas disponíveis para a IPM, há a própria radioterapia conformacional (Gatti et al, 2013;Goyal et al, 2013;Mózsa et al, 2014;Olivotto et al, 2013), a braquiterapia (Aristei et al, 2017;Hepel et al, 2014;Major et al, 2016;Ott et al, 2016;Polgár et al, 2017;Shah et al, 2018;Strnad et al, 2016) e a radioterapia intraoperatória com elétrons (IOeRT) (Veronesi et al, 2013). A radioterapia intraoperatória com fótons (IOpRT), também descrita na literatura, é, neste momento, de utilização desaconselhada.…”
Section: Introductionunclassified